(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article explores three key foreign language teaching methods: Grammar-Translation, Audiolingual, and Direct. Grammar-Translation focuses on grammar and reading, but neglects speaking. Audiolingual emphasizes drills for listening and speaking, influenced by behaviorism. The Direct Method promotes immersion and conversation, avoiding translation. While each method has strengths, they also face criticism for neglecting certain skills or being hard to implement. Despite the rise of the Communicative Approach, these methods remain relevant in specific educational contexts.